1998
DOI: 10.1136/gut.42.5.643
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous secretion of interferon γ and interleukin 4 by human intraepithelial and lamina propria gut lymphocytes

Abstract: (Gut 1998;42:643-649)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
49
1
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 24 publications
11
49
1
2
Order By: Relevance
“…A significant reduction in the total intestinal mucosa CD4+TL was observed in HIV+ patients, confirming previous studies (11,12,(30)(31)(32). This reduction did not correlate with disease stage, probably because of the small number of patients in group 2.…”
Section: Discussionsupporting
confidence: 76%
“…A significant reduction in the total intestinal mucosa CD4+TL was observed in HIV+ patients, confirming previous studies (11,12,(30)(31)(32). This reduction did not correlate with disease stage, probably because of the small number of patients in group 2.…”
Section: Discussionsupporting
confidence: 76%
“…The human gut mucosa seems to be in a state of controlled inflammation under normal conditions, since intestinal intraepithelial and lamina propria lymphocytes spontaneously secrete IFN-␥ (13,19,26). We observed that IFN-␥ dramatically increases the expression of TLRs and potentiates the capacity of DCs to secrete cytokines, but only in response to E. coli and V. parvula.…”
Section: Discussionmentioning
confidence: 61%
“…However, in normal LPL in humans, the in vitro response is dominated by IFN-␥ (28). Indeed, in previous studies from both us and others, the spontaneous production of cytokines by freshly isolated lamina propria T cells is dominated by IFN-␥ (29,30), and in our previous study of freshly isolated PP T cells, we also found an excess of IFN-␥-secreting cells (14).…”
Section: Discussionmentioning
confidence: 89%